Record of deeds, Camden County, 1882 - State of Georgia, Camden County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1882)
Record of deeds, Camden County, 1882. Handwritten record of deeds in pencil. Isabel Adams to E.J. Stafford, for tracts of land on Crow Harbor Island, Camden County, Georgia. December 4, 1882. 1 page.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Court records; Records and correspondence